A Legal Analysis Of The Restorative Justice Approach In Resolving Cases Involving Victims Of Drug Abuse At The Police Level (A Case Study In The Jurisdiction Of The Banten Provincial Police) - Marthin Naibaho; Benny Irawan; Rena Yulia (Universitas Dharmawangsa Medan, 2026)
This study aims to critically examine the implementation of the Restorative Justice approach in handling cases of drug abuse victims at the police level based on the Republic of Indonesia National Police Regulation Number 8 of 2021. The research method used is normative juridical with a descriptive-prescriptive nature and a statute approach. Data analysis was conducted qualitatively on primary, secondary, and tertiary legal materials. The results of the study indicate a fundamental conceptual paradigm conflict between the restorative justice mechanism in Police Regulation Number 8 of 2021 and the mandatory rehabilitation instrument contained in Law Number 35 of 2009 concerning Narcotics. In the law, rehabilitation tends to be constructed as part of the criminalization instrument (punitive), while the Police Regulation prioritizes investigative disclosure (non-litigation) for social recovery. In the implementation of the system, overlapping regulations between law enforcement institutions and unclear victimological parameters trigger legal openness and the risk of disparities in the field. This study concludes that a comprehensive revision of Police Regulation No. 8 of 2021 is necessary to harmonize technical regulations for victims of drug abuse and strengthen institutional synergy to achieve transparent substantive justice.